The efficiency of Nestle's distribution management at Confectionery and Pet Care Business Unit (CPBU), Bukit Raja / Mahadhir Ahmad Sanadi - Ahmad Sanadi, Mahadhir (1998)
Logistics is the collective term for the series of inter-related functions (principally transport, stockholding, storage, goods handling and order processing) involved in the physical transfer of finished products from producer to customer, directly or via intermediaries. Those elements involved are inter-related or a chain which the negligent of one of this activity, it will lead to the inefficiency of logistics as a whole. The principal tasks of logistics are to ensure that products are available at the right places, at the right time and in the right quantities to satisfy customers' demand